NEGOSIASI PERANG DAGANG AMERIKA SERIKAT DAN TIONGKOK - Sonia Agusti Parbo (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2020)
This study is analyzed the negotiation process trade war of the United States versus China under US foreign policy. This research is qualitative research, because it seeks to explain negotiate trade war between US and China. This research uses the research library for data collection through book, journal, and search engines and used analytical descriptive. The result of this study found that the trade war between US and China had a large impact on the global economy. Besides that, the trade war negotiation process aims to find a way out of the trade war. Negotiations between two countries reached a phase I agreement establish a “pause” of trade war